THE USE OF PADLET APPLICATION AS A MEDIA FOR MATHEMATICS LEARNING IN THE FACE-TO-FACE TIME IS LIMITED TO THE SETS MATERIALS IN CLASS VII SMP NEGERI 1 KUOK - Sutra Kasih; Efitha Asmana; Salmidar (Jurnal Prinsip Pendidikan Matematika, 2022)
As a result of COVID-19, face-to-face learning has been changed to distance learning and limited face-to-face learning. Students are required to learn online (online) because face-to-face is limited at school. In conditions of online learning (online/online) during the COVID-19 pandemic, an educator needs more appropriate learning media so that students can learn optimally. The purpose of this study was to determine the results of the evaluation of student learning by using appropriate mathematics learning media in the form of a Padlet application made by the teacher. This type of research used a qualitative descriptive method. The subjects of this study were students of class VIIa and VIIb of SMP Negeri 1 Kuok. Data collection techniques include: observation/observation, interviews, and documentation. Based on the results of the research that has been done, it can be concluded that learning without using the right media appears that students' understanding of the material is still lacking, this can be seen from the responses of students in the classroom from the observations of researchers during the study.